Evaluation of the Achievement of Minimum Service Standards at Az-Zahra Integrated Islamic Elementary School, Gorontalo City - Mansur Kasa; Abdul Kadim Masaong; Arwildayanto Arwildayanto (International Journal of Education, Culture, and Society, 2026)
Minimum Service Standards (SPM) for Basic Education serve as an important benchmark for assessing the quality of educational services at the school level. However, their implementation continues to face challenges, particularly in infrastructure provision, school management, and learning effectiveness. This study aims to evaluate the fulfilment of the Minimum Service Standards for Basic Education at SDIT Az-Zahra, Gorontalo City, using the Context, Input, Process, and Product (CIPP) evaluation model. A quantitative descriptive approach supported by qualitative data was employed. Data were collected through observation, interviews, documentation, and questionnaires, and were analyzed using descriptive percentage analysis to determine the achievement level of each evaluation component. The findings show that the fulfilment of SPM at SDIT Az-Zahra, Gorontalo City was generally categorized as sufficiently fulfilled, with an average achievement score of 74.91%. The context and input components each obtained 73.19%, the process component reached 73.75%, and the product component achieved the highest score at 79.51%. These results indicate that the school has demonstrated commitment to meeting SPM through data-driven planning, adequate learning implementation, and relatively high levels of learning outcomes and parental satisfaction. Nevertheless, several obstacles remain, particularly in infrastructure adequacy, School-Based Management implementation, academic supervision, and staff optimization. The study concludes that SPM implementation at SDIT Az-Zahra has been relatively successful but still requires systematic strengthening in management, educational resources, and learning service quality. This study contributes to educational quality evaluation by demonstrating the usefulness of the CIPP model in identifying school-level strengths and improvement priorities, with practical implications for data-driven planning, academic supervision, infrastructure improvement, and stakeholder engagement in the continuous enhancement of basic education services.